2021
DOI: 10.35542/osf.io/n8svc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three Cases That Demonstrate How Students Connect the Domains of Mathematics and Computing

Abstract: This study uses actor-oriented transfer to investigate different ways in which students make connections across the domains of mathematics and computing. We interview first-year students at the University of Oslo as they work with a set of tutorials that we designed to integrate knowledge from both domains. The cases we present here demonstrate four different types of cross-domain connections: (a) mathematically reproducing the work of a computer program, (b) cyclically improving a program to produce better ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In fact, researchers have already demonstrated that connections across the domains of mathematics and computing are made by students (Sand et al, 2021), and tools similar to the game here evaluated might be useful to support students' development of computational skills. The same metrics of maths scores also had a significant impact on students perceptions of challenge.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In fact, researchers have already demonstrated that connections across the domains of mathematics and computing are made by students (Sand et al, 2021), and tools similar to the game here evaluated might be useful to support students' development of computational skills. The same metrics of maths scores also had a significant impact on students perceptions of challenge.…”
Section: Conclusion and Discussionmentioning
confidence: 99%